Form of filters of semisimple modules and direct sums - Maturin, Yu. (Algebra and Discrete Mathematics, 2013)
Some collections of submodules of a module defined by certain conditions are studied. A generalization of the notion of radical (preradical) filter is considered. We study the form of filters of semisimple modules and direct sums.